Radial and Axial Profiles of Solids Concentration in a High-loaded Riser Reactor - Wirth, Karl-Ernst; Graßler, Thomas (Circulating Fluidized Bed Technology VI, 1999)
To characterize flow patterns in a high-loaded riser reactor a cold running plant with an inner diameter of 0.19 m and 15 m height has been built up. Experiments have been carried out with glass beads (mean diameter dp = 60 μm) at superficial gas velocities UG from 2 to 8 m/s which leads to solids mass fluxes Gs from 30 to 600 kg/m2s). Local information about the solids concentration distribution are obtained by an x-ray computed tomography system consisting of a 60 keV x-ray source and an x-ray linear detector with 1024 sensitive elements. Radial solids concentration profiles show the typical core-annulus structure of a riser. Results from x-ray CT have been area weighted and compared to an average solids concentration calculated from static pressure profiles. Both methods show good coincidence except at the exit of the riser where acceleration effects influence the pressure profiles. Radial and axial profiles of solids concentration distribution are compared for three different operating conditions. The typical core-annulus structure of the radial solids concentration distribution is more distinct at higher mass fluxes whereas the axial solids concentration profile is getting more equal. From axial pressure profiles the interstitial gas velocity has been calculated and was found to be almost constant over the whole height of the riser. Die Verf. beschreiben Versuchsergebnisse der gemessenen örtlichen Feststoffkonzentrationen und der statische Druckprofile in einem kalt betriebenen Steigrohr bei drei verschiedenen Versuchsbedingungen. Der Reaktor besaß einen Dmr. von 19 cm und eine Höhe von 15 m, als Feststoff wurden Glasperlen mit 0,6 cm Dmr. verwendet und die Gasgeschwindigkeit wurde von 2 bis 8 m/s variiert. Die Messungen erfolgten sowohl mit Röntgenstrahlung, die mit einem Computertomograph aufgezeichnet wurde, als auch über die Berechnung mittlerer Feststoffkonzentrationen aus den aufgenommen statischen Druckprofilen und zeigten gute Übereinstimmung.
UnivIS-Import:2015-04-20:Pub.1999.tech.ITC.mechve.radial_93
Keywords: riser; high-load; profile; x-ray analyzer; circulating fluidized bed; solid flow; riser reactor; gas flow; velocity field; Versuch; Reaktor; Steigrohr; Konzentration; Gas; Feststoff